2016
DOI: 10.1016/j.astropartphys.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic neutron background of nuclear emulsions for directional Dark Matter searches

Abstract: Recent developments of the nuclear emulsion technology led to the production of films with nanometric silver halide grains suitable to track low energy nuclear recoils with submicrometric length. This im- provement opens the way to a directional Dark Matter detection, thus providing an innovative and com- plementary approach to the on-going WIMP searches. An important background source for these searches is represented by neutron-induced nuclear recoils that can mimic the WIMP signal. In this paper we pro- vid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This study has also shown that the neutron-induced events can be reduced down to 0.06 kg −1 y −1 exploiting directionality and track length cuts. This result was obtained without any purification of the materials involved [37]. Nowadays ton-scale detectors for direct dark matter search have made the external neu-tron background negligible using appropriate shields.…”
Section: Background Sourcesmentioning
confidence: 73%
See 1 more Smart Citation
“…This study has also shown that the neutron-induced events can be reduced down to 0.06 kg −1 y −1 exploiting directionality and track length cuts. This result was obtained without any purification of the materials involved [37]. Nowadays ton-scale detectors for direct dark matter search have made the external neu-tron background negligible using appropriate shields.…”
Section: Background Sourcesmentioning
confidence: 73%
“…The main background sources is therefore induced by neutrons. Neutron-induced recoils from intrinsic contamination in NIT emulsions were recently evaluated with a GEANT4 simulation, giving a yield of ∼ 1 neutron kg −1 y −1 [37]. This study has also shown that the neutron-induced events can be reduced down to 0.06 kg −1 y −1 exploiting directionality and track length cuts.…”
Section: Background Sourcesmentioning
confidence: 94%
“…A pilot experiment will be performed with the exposure of 10 kg mass target on a time scale of one year with the aim of measuring the detectable background from environmental and intrinsic sources and to validate estimates from measurements [16] and simulations. The confirmation of a negligible background will pave the way for the construction of a pilot experiment with an exposure on the ∼10 kg year scale, which will act as a demonstrator to further extend the sensitivity towards the neutrino floor.…”
Section: Technical Test and Pilot Experimentsmentioning
confidence: 99%
“…The intrinsic emulsion radioactivity, instead, has been evalutated by using a dedicated MC simulation based on the SOURCES code [15] and a GEANT4-based simulation. The detectable neutron-induced background would be 0.06 n/yr/kg [16].…”
Section: Introductionmentioning
confidence: 99%
“…Detectors for anisotropic ultraenergetic cosmic rays of galactic origin are schematized in References [26][27][28]; the dark-matter-induced symmetry violations are examined in [29].…”
Section: Weak Gravitational Fieldsmentioning
confidence: 99%